2014
DOI: 10.3389/fnins.2014.00173
|View full text |Cite
|
Sign up to set email alerts
|

Visual context due to speech-reading suppresses the auditory response to acoustic interruptions in speech

Abstract: Speech reading enhances auditory perception in noise. One means by which this perceptual facilitation comes about is through information from visual networks reinforcing the encoding of the congruent speech signal by ignoring interfering acoustic signals. We tested this hypothesis neurophysiologically by acquiring EEG while individuals listened to words with a fixed portion of each word replaced by white noise. Congruent (meaningful) or incongruent (reversed frames) mouth movements accompanied the words. Indiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
10
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 35 publications
2
10
0
Order By: Relevance
“…This suggests that speech-reading may help restore phonetic representations of the degraded CI speech. Consistent with this premise, other studies that used speech with missing segments reported that speech-reading enhances the perception of continuity and intelligibility of the degraded speech (Benard & Başkent, 2015; Bhat, Pitt, & Shahin, 2014; Grant et al, 1998; Shahin, Bishop, & Miller, 2009; Shahin, Kerlin, Bhat, & Miller, 2012). …”
Section: Introductionsupporting
confidence: 53%
“…This suggests that speech-reading may help restore phonetic representations of the degraded CI speech. Consistent with this premise, other studies that used speech with missing segments reported that speech-reading enhances the perception of continuity and intelligibility of the degraded speech (Benard & Başkent, 2015; Bhat, Pitt, & Shahin, 2014; Grant et al, 1998; Shahin, Bishop, & Miller, 2009; Shahin, Kerlin, Bhat, & Miller, 2012). …”
Section: Introductionsupporting
confidence: 53%
“…As mentioned, the most widely used stimuli consist of phonetically matching and naturally timed AV speech. Therefore, data obtained with AV phonetic incongruent material (e.g., Alsius, Möttönen, Sams, Soto‐Faraco, & Tiippana, ), AV asynchronous stimuli (e.g., Huhn et al, ), or stimuli with artificial unimodal components (e.g., Baart, Stekelenburg, & Vroomen, ; Bhat, Pitt, & Shahin, ; Meyer, Harrison, & Wuerger, ) were excluded. Any work that did not include GAs for auditory speech as well as for AV(−V), or did not allow those conditions to be estimated, was excluded as well (Knowland, Mercure, Karmiloff‐Smith, Dick, & Thomas, ; Liu, Lin, Gao, & Dang, ; Magnée, de Gelder, van Engeland, & Kemner, ; Winkler, Horvath, Weisz, & Trejo, ), because study‐specific parameters that have an overall effect on the GAs can only be factored out when considering both A and AV(−V).…”
Section: Methodsmentioning
confidence: 99%
“…For example, older adults, who are known to have lower acoustic temporal resolution, show smaller N1-P2 AEPs compared to younger adults for the same gaps (Michalewski et al, 2005;Harris et al, 2012). Also, visually driven suppression of N1-P2 AEPs to onsets and offsets of gaps in speech reduces the temporal resolution to gaps and strengthens the perception of auditory continuity (Bhat et al, 2014).…”
Section: Significance Of Aep Amplitude Reductionmentioning
confidence: 99%